EFEKTIVITAS KEMITRAAN DENGAN METODE EKSPERIMEN PADA PENGOLAH IKAN KERING DI KABUPATEN REMBANG (BBM (Buletin Bisnis & Manajemen), 2015)
AbstractThis study aims to support the development of SMEs fish processing. The formulation of the issues raised are SMEs dried fish processors in determining the choice of form partnerships that benefit both parties, is able to distinguish the effectiveness of partnerships that were given a loan and that without being given a loan in advance. The hypothesis in this study suspected effectiveness of partnerships with first capital loaned able meningkatkkan performance so that the fish processing SME development in the coastal environment Rembang be increased. After testing the instrument with the results of all valid and reliable research instrument. From the results of the Kolmogorov-Smirnov test statistic and is based on the real level of 0,05 can be concluded that the data of SMEs in partnership with capitalized first is normal. Data normality test results SMEs with capitalized first Kolmogorov-Smirnov statistic is 0,070 and alpha of 0,05 means that H0 is accepted. Medium Data SMEs without prior dimodali Kolmogorov-Smirnov statistic of 0,082 and 0,200 significance alpha of 0,05 means that H0 is accepted. The results of the t test for SMEs which is capitalized in advance and that without statistical values obtained capital t = 2,944 and 0,004 significance value < 0,05. Because the significance value is smaller than the real level, we conclude H0 is rejected or no significance difference in SMEs which are given in advance and the capital without capitalized to increase performance so that the development of SMEs dried fish processors can increase sales and economic growth.